A pilot economic evaluation of computerized cognitive behavioral therapy for alcohol use disorder as an addition and alternative to traditional therapy. (27th April 2021) - Kacmarek, Corinne N.; Yates, Brian T.; Nich, Charla; Kiluk, Brian D.
Abstract: Background: Computer‐based delivery of cognitive behavioral therapy (CBT) may be a less costly approach to increase dissemination and implementation of evidence‐based treatments for alcohol use disorder (AUD). However, comprehensive evaluations of costs, cost‐effectiveness, and cost–benefit of computer‐delivered interventions are rare. Methods: This study used data from a completed randomized clinical trial to evaluate the cost‐effectiveness and cost–benefit of a computer‐based version of CBT (CBT4CBT) for AUD. Sixty‐three participants were randomized to receive one of the following treatments at an outpatient treatment facility and attended at least one session: (1) treatment as usual (TAU), (2) CBT4CBT plus treatment as usual (CBT4CBT+TAU), or (3) CBT4CBT plus brief monitoring. Results: Median protocol treatment costs per participant differed significantly between conditions, Kruskal‐Wallis H (2) = 8.40, p  = 0.02, such that CBT4CBT+TAU and CBT4CBT+monitoring each cost significantly more per participant than TAU. However, when nonprotocol treatment costs were included, total treatment costs per participant did not differ significantly between conditions. Median incremental cost‐effective ratios (ICERs) revealed that CBT4CBT+TAU was more costly and more effective than TAU. It cost $35.08 to add CBT4CBT to TAU to produce a reduction of one additional drinking day per month between baseline and the end of the 8‐week treatment protocol: CBT4CBT+monitoring cost $33.70 less to produce a reduction of one additional drinking day per month because CBT4CBT+monitoring was less costly than TAU and more effective at treatment termination, though not significantly so. Net benefit analyses suggested that costs of treatment, regardless of condition, did not offset monthly costs related to healthcare utilization, criminal justice involvement, and employment disruption between baseline and 6‐month follow‐up. Benefit–cost ratios were similar for each condition. Conclusions: Results of this pilot economic evaluation suggest that an 8‐week course of CBT4CBT may be a cost‐effective addition and potential alternative to standard outpatient treatment for AUD. Additional research is needed to generate conclusions about the cost–benefit of providing CBT4CBT to treatment‐seeking individuals participating in standard outpatient treatment. Abstract : Most people struggling with alcohol use disorder (AUD) cannot access treatment. A pilot economic evaluation of computer‐based cognitive behavioral therapy (CBT4CBT) for AUD demonstrated that an 8‐week course of CBT4CBT may be a cost‐effective addition or alternative to standard outpatient treatment as usual (TAU). At treatment termination, incremental cost‐effective ratios suggested that CBT4CBT+TAU was more costly and effective, and CBT4CBT+monitoring was less costly and more effective, than TAU. Computer‐based treatment has the potential to expand access to evidence‐based treatment for AUD.